2012
DOI: 10.1007/s12033-012-9545-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Protein Secretion From Insect Cells by Co-Expression of the Chaperone Calreticulin and Translation Initiation Factor eIF4E

Abstract: Host protein synthesis is shut down in the lytic baculovirus expression vector system (BEVS). This also affects host proteins involved in routing secretory proteins through the endoplasmic reticulum (ER)-Golgi system. It has been demonstrated that a secretory alkaline phosphatase-EGFP fusion protein (SEFP) can act as a traceable and sensitive secretory reporter protein in BEVS. In this study, a chaperone, calreticulin (CALR), and the translation initiation factor eIF4E were co-expressed with SEFP using a bicis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Colocalization and immunoprecipitation experiments indicated that in uninfected mosquito cells, CAV-1 is indeed associated with all 3 chaperones proposed to form the complex, FKPB52, Cy40, and CyA; moreover, knocking down the expression of CAV-1 (data not shown) or any of the associated chaperones resulted in a significant decrease in the lipid droplet count per cell, indicating a role for the CCC in lipid homeostasis in mosquito cells. In agreement with our results, ER chaperones have been reported to be necessary for the secretion of recombinant proteins expressed in insect cells using a baculovirus system (30,31).…”
Section: Discussionsupporting
confidence: 93%
“…Colocalization and immunoprecipitation experiments indicated that in uninfected mosquito cells, CAV-1 is indeed associated with all 3 chaperones proposed to form the complex, FKPB52, Cy40, and CyA; moreover, knocking down the expression of CAV-1 (data not shown) or any of the associated chaperones resulted in a significant decrease in the lipid droplet count per cell, indicating a role for the CCC in lipid homeostasis in mosquito cells. In agreement with our results, ER chaperones have been reported to be necessary for the secretion of recombinant proteins expressed in insect cells using a baculovirus system (30,31).…”
Section: Discussionsupporting
confidence: 93%
“…Gantke et al co-expressed the Ebola virus protein 35, which is a viral protein that prevents translational silencing, and increased recombinant protein production by 10-fold [16]. An alternative approach to circumvent translational silencing in insect cells following baculovirus infection is to co-express eIF4E, which resulted in a 2-fold increase in the production of a secreted alkaline phosphatase (SEAP)-EGFP fusion protein (SEFP)[17]. …”
Section: Optimizing Transcription and Enhancing Translationmentioning
confidence: 99%
“…In insect cells, host protein biosynthesis shuts down as a result of infection by the recombinant baculovirus, which can adversely affect levels of molecular chaperones important for the folding of secreted proteins and membrane proteins in the endoplasmic reticulum (ER), particularly in relation to the high levels of protein synthesis resulting from high mRNA levels produced from the polyhedrin promoter. Hence, co-expression of the membrane-bound molecular chaperone calnexin enhanced the expression of functional serotonin transporter (SERT) by nearly 3 fold [21], and co-expression of the soluble molecular chaperone calreticulin increased secretion of SEFP in insect cells [17]. Whether a lack of appropriate molecular chaperones in heterologous systems contributes to low levels of functional protein sometimes is difficult to assess.…”
Section: Folding and Secretory Pathway Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this shutdown leads to molecular chaperone and foldase insufficiencies in the ER, which in turn result in protein aggregation (Fath-Goodin et al, 2006;Teng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%